Physico-Chemical Studies on Chimdi Lake of Sunsari District during its Restoration Stage - Surana, R.; Subba, B.R; Limbu, K.P (Our Nature, 2011)
Chimdi Lake was ecologically a valuable site but due to the exploitation, almost all parts of the Lake changed into a terrestrial habitat. The issues of lake conservation have been brought into light recently and the work for rehabilitation; protection and conservation have been initiated by local peoples. Water quality plays an important role in determining the biodiversity of any water body. Various physico-chemical parameters such as atmospheric temperature, water temperature, transparency, total solids, total dissolved solids, total suspended solids, humidity, pH, dissolved oxygen, free carbon dioxide, total alkalinity, acidity, total hardness, calcium hardness, calcium, magnesium and chloride were estimated on monthly basis from March 2004 to February 2005. Physico- chemical values revealed that the lake is a suitable site for the habitat of aquatic lives. DOI: 10.3126/on.v8i1.4337